Fine-Needle Aspiration Cytology of Parathyroid Carcinoma Mimic Hürthle Cell Thyroid Neoplasm. (10th August 2014) - Sriphrapradang, Chutintorn; Sornmayura, Pattana; Chanplakorn, Niramol; Trachoo, Objoon; Sae-Chew, Pattarana; Aroonroch, Rangsima
Abstract : Background . Fine-needle aspiration (FNA) can cause misdiagnosis of cytomorphological findings between parathyroid and thyroid lesions. Case Presentation . A 31-year-old man presented with a palpable neck mass on the right thyroid lobe. FNA cytology was reported as intrathyroidal lymphoid hyperplasia. After 5 years, repeated FNA was done on the enlarged nodule with result of Hürthle cell lesion. Prior to right lobectomy, laboratories revealed elevated serum calcium and parathyroid hormone (PTH). Careful history taking revealed chronic knee pain and ossifying fibroma at the maxilla. Ultrasonography showed a 2.8 cm mass inferior to right thyroid lobe. Pathology from en bloc resection was parathyroid carcinoma and immunohistochemical study revealed positivity for PTH. Genetic analysis found somatic mutation of CDC73 gene in exon1 (c.70delG) which caused premature stop codon in amino acid 26 (p . Glu 24 Lysfs 2 * ). The final diagnosis was hyperparathyroidism-jaw tumor syndrome. Conclusions . FNA cytology of parathyroid can mimic thyroid lesion. It is important to consider and correlate the entire information from clinical history, laboratory, imaging, and FNA.